Spatiotemporal Subpixel Geographical Evolution Mapping - He, Da; Zhong, Yanfei; Zhang, Liangpei (IEEE transactions on geoscience and remote sensing, 2019)
In recent decades, spatiotemporal subpixel mapping (SSM) approaches have been extensively developed to deal with the mixed-pixel problem by incorporating fine spatial resolution images with the same field of view from different acquisition times. This is an alternative to the conventional subpixel mapping (SPM) method, which is based on only monotemporal images. SSM has become one of the state-of-the-art SPM approaches, and has been widely applied in urban management and ecological monitoring. However, in the traditional SSM methods, the spatial correlation within the multitemporal images is insufficiently exploited and is ignored in the spatiotemporal model construction. In addition, the contribution of the land covers' spatial distribution in the multitemporal images is incompletely considered, and the geographic variation during the time interval is ignored, which underutilizes the spatiotemporal information. In this paper, an SSM algorithm based on a geographically weighted regression (GWR) model and evolutionary algorithm theory, called spatiotemporal subpixel geographical evolution mapping (STGEM), is proposed for multitemporal remote sensing images. The proposed algorithm considers the spatiotemporal dependence not only between the current subpixel and the corresponding fine pixel, but also with the neighboring fine distribution patterns within the fine image. Moreover, the potential temporal information of the geospatial variation is fully realized by considering not only the time interval between the bitemporal images, but also the ratio of changed area between them, based on the GWR model. Two synthetic-image experiments with bitemporal Landsat 8 images and bitemporal QuickBird images were carried out to validate the proposed algorithm. Furthermore, a real-image experiment using a bitemporal pair of Gaofen-2 images and a Landsat 8 image was also undertaken. A comparison was made with several traditional SPM methods, as well as the state-of-the-art SSM approaches, and the experimental results confirmed the superiority of the proposed STGEM algorithm. The proposed STGEM achieves a fine spatial and temporal resolution thematic map, both qualitatively and quantitatively, and has great potential for fine-scale and frequent time-series observation and monitoring.